Molecular strategies for control of cymbidium mosaic virus / Adriya binti Dzulkurnain @ Hamidi - Dzulkurnain @ Hamidi, Adriya (2013)
Orchid, amongst the most popular flowers in the world, play a major role in the economy of many Asian countries. However, detrimental effects by various viruses can reduce the economic value of this horticultural crop. There have been a number of viruses known to occur in orchids globally with one of the most common being Cymbidium mosaic virus (CymMV). Plant genetic engineering approaches have been successful in producing crops with viral resistance, however there has been a concern expressed that resistance resulting from single gene constructs might be rather narrow (specific to only certain virus sub-type) could easily break down. Thus this research aimed to develop a multiple strategy approach towards the control of CymMV in orchids by combining the concepts of pathogen derived resistance and antibody mediated resistance. A plant transformation vector, pCAMBIA 1304-CymMV-fwd was constructed to contain coat protein sequences from the CymMV. The construct was successfully transformed into explant samples and RT-PCR analysis showed that the pathogen derived resistance sequence was successfully expressed in plants. In a second part to the study anti-CymMV was isolated from a Toxoplasma gondii-immunized single-chain variable fragment (ScFv) antibody phage-display library. Four antibodies were isolated and analyzed through BLASTX and nucleotide BLAST but only one provided significant similarity to PDPK1 3-phosphoinositide dependent protein kinase-1 [Homo sapiens]. The two genes have the potential to be pyramided together in a single plant transformation vector, or to be introduced into plants by successive transformation, in order to develop orchids with longer term viral resistance.